2010
DOI: 10.1093/occmed/kqp196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood transmission through latex and nitrile glove materials

Abstract: AimsTo compare blood transmission through nitrile, single and double layer latex glove materials in simulated needlestick injuries. MethodsExperiments involved nitrile, single and double layer latex gloves. A cutting suture needle was dipped into a specimen of blood and then immediately jabbed through the glove material into a cell containing saline. This process was repeated using the same blood specimen with different glove materials, plus a control experiment with no glove material. Other factors, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This study also found that 34.2% of students did not always wear gloves when they drew blood from patients. Gloving is known to protect against injury from needles, (17) as well as reduce the risk of blood-borne infections to healthcare workers due to the 'wiping effect' of the glove material. (18) Gloving reduces the risk of blood-borne infections because it can reduce the volume of contaminated blood being introduced by injury due to hollow-bore needles.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that 34.2% of students did not always wear gloves when they drew blood from patients. Gloving is known to protect against injury from needles, (17) as well as reduce the risk of blood-borne infections to healthcare workers due to the 'wiping effect' of the glove material. (18) Gloving reduces the risk of blood-borne infections because it can reduce the volume of contaminated blood being introduced by injury due to hollow-bore needles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, apart from being exposed during the needlestick injuries, venous blood sampling is always associated with a risk for blood contact and contamination during the procedure. There is evidence showing that this risk is reduced using gloves [45,46]. It has been shown that hand cleansing is the key to the reducing the risk of the infection of the healthcare staff and crosstransmission of antimicrobial resistant pathogens.…”
Section: Samplingmentioning
confidence: 99%
“…The direct constrictive/frictional contact of the needle with the film is evident and should therefore facilitate a physical cleansing action. In cases of deep puncture involving either hollow bore or suture needle, there were no additional gains in puncture protection with double gloving [40,41], but that may not be true in the case of MN arrays. The presence of a glove will certainly reduce the degree to which a needle will puncture, but their influence is potentially greater in the context of MNs where the length of the needles is greatly reduced.…”
Section: Discussionmentioning
confidence: 97%